British Association of Dermatologists guidelines for biologic therapy for psoriasis 2017. (1st September 2017) - Smith, C.H.; Jabbar‐Lopez, Z.K.; Yiu, Z.Z.; Bale, T.; Burden, A.D.; Coates, L.C.; Cruickshank, M.; Hadoke, T.; MacMahon, E.; Murphy, R.; Nelson‐Piercy, C.; Owen, C.M.; et al.
Abstract: Plain language summary available online